Beryllium sulfur doped with N, Li and Na: Promising p-type transparent semiconductor. (September 2021) - Wang, Z.L.; Fan, S.W.
Abstract: The properties for group IA and VA atoms doped BeS are studied by using the first-principles method. Our studies show BeS is a transparent semiconductor. The visible light transmittances could reach 80.0 %, as the thickness increases to 60.0 nm. The holes effective mass along the Г-X and Г-L directions are 0.56 and 1.34 m0 (m0 is electron's static mass). The defective behaviors for group IA and VA atoms in BeS show that N substituting S, together with the Li and Na substituting Be are shallow acceptors, and the corresponding ionization energy levels ε(0/-), compared to the valence band maximum, are 0.166, 0.177 and 0.25 eV, respectively. Formation energies imply under S-rich condition, NS, LiBe and NaBe defects can be realized experimentally by using the equilibrium growth conditions, while the detrimental hole killers, such as, VS, Bei, Nint, Liint and Naint would be inhibited as samples fabrication. These properties indicate N, Li and Na doped BeS may offer new opportunities in transparent electronics and optoelectronic applications.